2018
DOI: 10.1098/rspb.2018.1788
|View full text |Cite
|
Sign up to set email alerts
|

A non-coding region near Follistatin controls head colour polymorphism in the Gouldian finch

Abstract: Discrete colour morphs coexisting within a single population are common in nature. In a broad range of organisms, sympatric colour morphs often display major differences in other traits, including morphology, physiology or behaviour. Despite the repeated occurrence of this phenomenon, our understanding of the genetics that underlie multi-trait differences and the factors that promote the long-term maintenance of phenotypic variability within a freely interbreeding population are incomplete. Here, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…Consistent with our findings, studies in reptiles and birds have found that colour polymorphisms can often be explained by a single major effect locus [38,43]. The role of a single gene in driving differences between colour morphs is surprising given that morphs often show correlated differences in other key traits [38,43]. Indeed, differences in reproduction, predation, and physiology have been associated with carotenoid pigmentation in salmonids [16][17][18][19][44][45][46][47].…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with our findings, studies in reptiles and birds have found that colour polymorphisms can often be explained by a single major effect locus [38,43]. The role of a single gene in driving differences between colour morphs is surprising given that morphs often show correlated differences in other key traits [38,43]. Indeed, differences in reproduction, predation, and physiology have been associated with carotenoid pigmentation in salmonids [16][17][18][19][44][45][46][47].…”
Section: Discussionsupporting
confidence: 82%
“…Linked-read sequencing has a huge potential for generating decent draft bird genome assemblies (Toomey et al 2018, Boman et al 2019, Kinsella et al 2019, Lutgen et al 2020. 10X Genomics Chromium is the most commonly used linked-read library preparation at present, but other linked-read methods , Redin et al 2019 are equally promising but have yet to be tested on birds.…”
Section: Resultsmentioning
confidence: 99%
“…First, both independent approaches highlight the same genomic region upstream of the follistatin gene, providing strong evidence of its functional role in generating the colour polymorphism. Second, unlike Toomey et al 52 , our analysis incorporates data from wild birds, making clear the relevance of this region to nondomesticated populations. Finally, our simulations and evolutionary reconstructions add key historical context to how and why this polymorphism has evolved and is maintained in the wild.…”
Section: The Evolutionary History Of the Black And Red Haplotypesmentioning
confidence: 99%